EXPLORING THE EXPERIENTIAL MEANING OF SONG LYRICS: A SYSTEMATIC LITERATURE REVIEW - Simbolon, Lasyuli; Suhadi, Jumino; Pratiwy, Devi (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This paper presents a systematic literature review exploring the experiential meaning of song lyrics, focusing on studies published between 2020 and 2024. Drawing from 21 peer-reviewed articles, the review synthesizes how song lyrics encode and convey lived experience through linguistic and cultural mechanisms. The analysis reveals that Systemic Functional Linguistics (SFL), particularly transitivity analysis, is the predominant framework used to examine how mental, relational, and material processes construct experiential meaning in lyrics. Additionally, figurative language such as metaphor and personification plays a vital role in symbolizing complex emotions and psychological states. Beyond individual expression, song lyrics are also shown to reflect broader sociocultural narratives related to identity, gender, and power dynamics. These findings underscore the multifaceted nature of experiential meaning, highlighting the interplay between grammatical structures, stylistic devices, and cultural contexts. The review also identifies gaps in the literature, notably the need for more cross-cultural studies and listener reception research. Finally, the paper discusses the pedagogical potential of song lyrics for language learning and suggests future directions integrating multimodal and interdisciplinary approaches. This review contributes to a deeper understanding of how songs serve as powerful vehicles for sharing and interpreting human experience.